La gestión del talento humano y su incidencia en el desempeño del personal de la empresa Peelgood, en la parroquia Izamba, cantón Ambato, parroquia Izamba, provincia Tungurahua, año 2024 - Santos Nuela, Kevin Omar (2024)
The present research work called Human Talent Management and its impact on the performance of the staff of the Peelgood company, in the Izamba parish, Ambato canton, Tungurahua province, year 2024, focuses on improving the work performance of collaborators through of effective human talent management. This management seeks to motivate employees to accomplish their tasks efficiently, which leads to better organizational functioning and greater collaborative efficiency. The research work focuses on defining the most relevant aspects of Human Talent Management and job performance, with the objective of proposing alternatives to address the deficiencies in the Peelgood company and meet its individual and organizational objectives. The 180° Evaluation Model for the Peelgood company includes important guidelines aimed at improving work performance, which will be implemented in both employees and managers of the organization. As part of the proposal, a specific evaluation model will be developed, for which the necessary steps for its implementation will be formulated.